Effect Of Dietary Supplementation Of Ascorbic Acid On Physiological Parameters, Body Weight Changes And Reproductive Performance Of Swamp Buffaloes (Applied Biological Research, 2016)
To assess the effect of ascorbic acid supplementation on physiological  parameters in buffalo viz., changes in body weight, dry matter intake and  reproductive performances, eighteen Swamp buffaloes were divided into  three groups. One group was fed with normal diet and other two groups  supplemented with 10 and 15 g ascorbic acid animal-1 day-1. The group  supplemented with 15 g ascorbic acid animal-1 day-1 had significantly lower  respiration rate, pulse rate and rectal temperature as compared to the  group supplemented with 10 or 0 g ascorbic acid animal-1 day-1. The dry  matter intake kg-1 body weight, DMI per kg W0.75 was not affected by  cent of animals coming  into oestrus, conception rate and number of services per conception  improved at higher level of ascorbic acid supplementation. It may be  concluded that dietary supplementation of ascorbic acid has favourable  impact in maintaining the physiological parameters, body weight and improved reproductive traits of swamp buffaloes.
Keywords: Ascorbic acid; physiology; reproductive traits; swamp buffalo